Characterization of Endophytic Diazotroph Bacteria Isolated from Rice - JOKO PRAYITNO; BARRY ROLFE (Bogor Agricultural University, Indonesia, 2010)
Attempt to extend the biological nitrogen fixation to important crops such as rice has been conducted by isolating endophytic diazotrophs from rice rhizosphere and roots. In this study, three bacterial isolates of R2, R4, and E4 isolated from rice-legume rotation in the Nile Delta Egypt and four bacterial isolates of R38-O, R38-T, R53, and R58 isolated from wild rice in the Philippines were characterized using classical methods of bacterial identification and using biochemical test kits (API20E and API20NE). R2 and R4 isolates were identified as Rhizobium sp., E4 isolate was identified as Rhizobium leguminosarum bv. trifolii, and R38-T, R53, and R58 isolates were identified as Sphingomonas, Azospirillum, and Agrobacterium, respectively. Of all Rhizobium isolates, only E4 could form nodules on legumes other than their original host berseem clover (Trifolium alexandrum L.) as their original host.